New vegetable oil blends to ensure high biological value and oxidative stability - Nosenko, Tamara; Shemanska, Evgeniya; Bakhmach, Volodymyr; Sidorenko, Taisiya; Demydova, Anastasiya; Berezka, Tetyana; Arutyunyan, Tetyana; Matukhov, Dmitrij (Eastern-European Journal of Enterprise Technologies, 2017)
The compositions of fatty acids of 15 types of vegetable oils of cold pressing have been studied to develop and justify the blends of sunflower oil with camelina oil, flaxseed oil and walnut oil as those that have reasonable ratios of ω-3:ω-6 polyunsaturated fatty acids. The autocatalytic oxidation of the blends was studied at a storage temperature of (20±2) ºС with free access of light and air. A significant slowdown in the rate of accumulatng peroxides and free fatty acids was established when blending 45 % of walnut oil or 40 % of camelina oil with the appropriate amount of sunflower oil. The developed blend of 55 % of sunflower oil plus 45 % of walnut oil has been found to have a ratio of ω-3:ω-6 polyunsaturated fatty acids close to that recommended for daily nutrition. Blends of vegetable oils with a higher ratio of ω-3:ω-6 fatty acids (75 % of sunflower oil plus 25 % of flaxseed oil and 60 % of sunflower oil plus 25 % of camelina oil) are recommended by the authors for therapeutic nutrition. Blending of traditional sunflower oil with other types of vegetable oils makes it possible to solve two problems – to increase the biological value of fat by optimizing the fatty acid composition and to increase resistance to oxidative spoilage. The developed blends of sunflower oil with walnut oil or camelina oil are stable to oxidation, so they can be recommended for making health-improving products.